Microbiological Aspects of Root Canal Infections and Disinfection Strategies: An Update Review on the Current Knowledge and Challenges - Jasmine Wong; Daniel Manoil; Peggy Näsman; Georgios N. Belibasakis; Prasanna Neelakantan (Frontiers Media S.A., 2021)
The oral cavity is the habitat of several hundreds of microbial taxa that have evolved to coexist in multispecies communities in this unique ecosystem. By contrast, the internal tissue of the tooth, i.e., the dental pulp, is a physiologically sterile connective tissue in which any microbial invasion is a pathological sign. It results in inflammation of the pulp tissue and eventually to pulp death and spread of inflammation/infection to the periradicular tissues. Over the past few decades, substantial emphasis has been placed on understanding the pathobiology of root canal infections, including the microbial composition, biofilm biology and host responses to infections. To develop clinically effective treatment regimens as well as preventive therapies, such extensive understanding is necessary. Rather surprisingly, despite the definitive realization that root canal infections are biofilm mediated, clinical strategies have been focused more on preparing canals to radiographically impeccable levels, while much is left desired on the debridement of these complex root canal systems. Hence, solely focusing on "canal shaping" largely misses the point of endodontic treatment as the current understanding of the microbial aetiopathogenesis of apical periodontitis calls for the emphasis to be placed on "canal cleaning" and chemo-mechanical disinfection. In this review, we dissect in great detail, the current knowledge on the root canal microbiome, both in terms of its composition and functional characteristics. We also describe the challenges in root canal disinfection and the novel strategies that attempt to address this challenge. Finally, we provide some critical pointers for areas of future research, which will serve as an important area for consideration in Frontiers in Oral Health.